2014
DOI: 10.1177/2158244014553584
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Identity Development, Principled Moral Reasoning, and Empathy as Predictors of Openness to Diversity in Emerging Adults

Abstract: There are many paths to enlightenment.-Lao Tzu, Chinese Taoist philosopher (600-531 BC) Long-studied in social psychology, the dangers of prejudice (Allport, 1954) and the importance of developing tolerance and respect for others have received attention with an increased sense of urgency over the past decade. Globally, although distances are ever-shrinking and differing cultures must cooperate for survival, terrorist threats and genocidal wars are part of the daily news. Within the United States, although popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 74 publications
1
21
0
3
Order By: Relevance
“…Generally, EAs showed positive mean levels of MCI, tolerance and PCI in both contexts. This confirms that emerging adulthood may be a particularly fruitful time to facilitate the acceptance of others (Gerson & Neilson, ). Nevertheless, the attitudes towards the specific immigrant groups selected in this study were in line with the common views of these groups in Italy, where the highest anti‐Roma attitudes in Europe are registered (Pew Research Center, ) and Romanian and Maghrebi people are viewed unfavourably by a substantial part of population (Italian National Institute of Statistics, ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Generally, EAs showed positive mean levels of MCI, tolerance and PCI in both contexts. This confirms that emerging adulthood may be a particularly fruitful time to facilitate the acceptance of others (Gerson & Neilson, ). Nevertheless, the attitudes towards the specific immigrant groups selected in this study were in line with the common views of these groups in Italy, where the highest anti‐Roma attitudes in Europe are registered (Pew Research Center, ) and Romanian and Maghrebi people are viewed unfavourably by a substantial part of population (Italian National Institute of Statistics, ).…”
Section: Discussionsupporting
confidence: 69%
“…Such a task requires knowledge, attitudes and skills respectful of the differences among people (Devine, Green, & McDowell, ). In this sense, few studies (i.e., Gerson & Neilson, ; King & Baxter Magolda, ) examined intercultural relations of emerging adults (EAs), the group of 18–29 year‐olds who are between adolescence and adulthood (Arnett, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies already found some personal predictors that influence the development of tolerance, i.e. empathy (empathic concern) and personality (Openness and Agreeableness) (Butrus & Witenberg, 2012;Gerson & Neilson, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The other personal factor is psychosocial development of the "intimacy vs isolation" stage. A previous study stated that young adults are the stage where they can have more opportunities to interact with more diverse individuals compared with the other life stages (Gerson & Neilson, 2014). These interactions then lead the person to have a higher interest in others that come from different backgrounds, for example others with different ethnicities.…”
Section: Introductionmentioning
confidence: 99%